Overexpression of the β Subunit of Human Chorionic Gonadotropin Promotes the Transformation of Human Ovarian Epithelial Cells and Ovarian Tumorigenesis - Guo, Xiaoqing (American Society for Investigative Pathology, 2011)
Ovarian carcinoma is the most lethal gynecologic malignancy, however underlying molecular events remain elusive. Expression of human chorionic gonadotropin β subunit (β-hCG) is clinically significant for both trophoblastic and nontrophoblastic cancers; however, whether β-hCG facilitates ovarian epithelial cell tumorigenic potential remains uncharacterized. Immortalized nontumorigenic ovarian epithelial T29 and T80 cells stably overexpressing β-hCG were examined for alterations in cell cycle and apoptotic status by flow cytometry, expression of proteins regulating cell cycle and apoptosis by Western blot, proliferation status by MTT assay, anchorage-independent colony formation, and mouse tumor formation. Immunoreactivity for β-hCG was evaluated using mouse xenografts and on human normal ovarian, fallopian tube, endometrium, and ovarian carcinoma tissues. T29 and T80 cells overexpressing β-hCG demonstrated significantly increased proliferation, anchorage-independent colony formation, prosurvival Bcl-X(L) protein expression, G2-checkpoint progression, elevated cyclins E/D1 and Cdk 2/4/6, and decreased apoptosis. Collectively, these transformational alterations in phenotype facilitated increased xenograft tumorigenesis (P < 0.05). Furthermore, β-hCG immunoreactivity was elevated in malignant ovarian tumors, compared with normal epithelial expression in ovaries, fallopian tube, and endometrium (P < 0.001). Our data indicate that elevated β-hCG transforms ovarian surface epithelial cells, facilitating proliferation, cell cycle progression, and attenuated apoptosis to promote tumorigenesis. Our results further decipher the functional role and molecular mechanism of β-hCG in ovarian carcinoma. β-hCG may contribute to ovarian cancer etiology, which introduces a new therapeutic intervention target for ovarian cancer.